Change is gonna come: a mixed methods examination of people's attitudes toward prisoners after experiences with a prison choir - Messerschmidt, Edward David (2017)
The purpose of this study was to examine the effects of (a) singing with incarcerated choir members and (b) listening to a live prison choir performance, on non-incarcerated people, focusing particularly on the effects of such experiences on participants’ attitudes toward prisoners. Participants included: 1) non-incarcerated volunteer singers from four Midwestern prison choirs (n = 41); 2) a control group of Midwestern community choir members who, at the time of data collection, had had no experiences in a prison context or with a prison choir (n = 19); and 3) non-incarcerated, adult audience members at a Midwestern prison choir concert (n = 78). In part 1 of the study, the volunteer singers and control group completed the Attitude toward Prisoners scale (ATPS; Melvin et al., 1985) and responded to two open-ended items following the completion of their respective spring concerts. In part 2 of the study, adult audience members completed the ATPS (Melvin et al., 1985) before and after attending a Midwestern prison choir concert. After the concert, the audience members also responded in writing to an open-ended item regarding their experience at the performance. Research questions included: 1. How do the ATPS scores of the volunteer prison choir singers compare to the ATPS scores of the control group? What is the relationship between participation in a prison choir and ATPS scores? 2. What relationship, if any, is there between the number of concerts the volunteer singers have sung with a prison choir and their ATPS scores? 3. What changes, if any, are there between audience members’ pre-test and post-test responses to the ATPS (Melvin et al., 1985)? 4. What effects, if any, do volunteer singers and audience members report regarding their experiences with a prison choir? Using mixed methods in a concurrent triangulation design (Harwell, 2011), the researcher found that it is possible for non-incarcerated people to change their attitudes toward prisoners through experiences with a prison choir. Although there was not a significant difference between the ATPS scores of non-incarcerated volunteer prison choir singers and those of the non-prison-based community choristers, 69.2% of the volunteer prison choir singers reported that their attitudes toward prisoners had grown more positive since joining a prison choir. Alternatively, in part 2 of the study, audience members’ ATPS scores were significantly more positive after attending the prison choir concert. Using an open, axial, and selective coding process (Charmaz, 2006) to analyze open-ended responses in both parts of the study, the researcher developed an informed grounded theory (Thornberg, 2012) that musical activities with a prison choir (including both singing and listening) afford people the opportunity to explore their sense of ideal relationships; through that exploration, their sense of ideal relationships can either be affirmed or challenged (Small, 1998), which, in the latter case, can potentially lead to a change in their attitudes toward prisoners. The results of this study could be particularly important to music educators seeking to meet the NAfME (2017) goal of “music for all,” as well as to researchers interested in criminal justice reform. After all, negative attitudes toward prisoners influence criminal justice policy (Melvin et al., 1985) and are also an impediment to tertiary desistance (Nugent & McNeill, 2017) and newly released prisoners’ successful reintegration into society (Hirschfield & Piquero, 2010; Park, 2009)